Cicadas (of Florida), Neocicada hieroglyphica (Say), Tibicen, Diceroprocta and Melampsalta spp. (Insecta: Hemiptera: Cicadidae) - Thomas J. Walker; Thomas Moore (EDIS)
In Florida, cicadas are best known for their loud calls heard during the day, usually issuing from trees. Their cast nymphal skeletons are often seen on the trunks of trees or on shrubs. In much of the eastern United States, they are also known for their appearance in colossal numbers (as many as 1.5 million per acre) every 13 or 17 years. Although these periodical cicadas (Magicicada spp.) do not occur in Florida, they merit further discussion under Life Cycles. This document is EENY-327, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 2004. Revised: September 2004.